Respuesta :

Answer:

FH = 134

Step-by-step explanation:

From the question given:

G is the midpoint of FH

FG = 14x + 25

GH = 73 - 2x

FH =?

Next, we shall determine the value of x. The value of x can be obtained as follow:

Since G is the midpoint of FH, this implies that FG and GH are equal i.e

FG = GH

With the above formula, we can obtain the value of x as follow:

FG = 14x + 25

GH = 73 - 2x

x =?

FG = GH

14x + 25 = 73 - 2x

Collect like terms

14x + 2x = 73 - 25

16x = 48

Divide both side by 16

x = 48/16

x = 3

Next, we shall determine the value of FG and GH. These can be obtained as shown below:

FG = 14x + 25

x = 3

FG = 14x + 25

FG = 14(3) + 25

FG = 42 + 25

FG = 67

GH = 73 - 2x

x = 3

GH = 73 - 2x

GH = 73 - 2(3)

GH = 73 - 6

GH = 67

Finally, we shall determine FH as follow:

FH = FG + GH

FG = 67

GH = 67

FH = FG + GH

FH = 67 + 67

FH = 134

Therefore, FH is 134